Combination of two anti‐CD5 monoclonal antibodies synergistically induces complement‐dependent cytotoxicity of chronic lymphocytic leukaemia cells. (8th August 2013) - Klitgaard, Josephine L.; Koefoed, Klaus; Geisler, Christian; Gadeberg, Ole V.; Frank, David A.; Petersen, Jørgen; Jurlander, Jesper; Pedersen, Mikkel W.
Summary The treatment of chronic lymphocytic leukaemia (CLL) has been improved by introduction of monoclonal antibodies (mAbs) that exert their effect through secondary effector mechanisms. CLL cells are characterized by expression of CD5 and CD23 along with CD19 and CD20, hence anti‐CD5 Abs that engage secondary effector functions represent an attractive opportunity for CLL treatment. Here, a repertoire of mAbs against human CD5 was generated and tested for ability to induce complement‐dependent cytotoxicity (CDC) and antibody‐dependent cell‐mediated cytotoxicity (ADCC) both as single mAbs and combinations of two mAbs against non‐overlapping epitopes on human CD5. The results demonstrated that combinations of two mAbs significantly increased the level of CDC compared to the single mAbs, while no enhancement of ADCC was seen with anti‐CD5 mAb combinations. High levels of CDC and ADCC correlated with low levels of Ab‐induced CD5 internalization and degradation. Importantly, an anti‐CD5 mAb combination enhanced CDC of CLL cells when combined with the anti‐CD20 mAbs rituximab and ofatumumab as well as with the anti‐CD52 mAb alemtuzumab. These results suggest that an anti‐CD5 mAb combination inducing CDC and ADCC may be effective alone, in combination with mAbs against other targets or combined with chemotherapy for CLL and other CD5‐expressing haematological or lymphoid malignancies.